2015
DOI: 10.1002/ana.24522
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of preoperative and early postoperative seizures in patients with intra‐axial primary and metastatic brain tumors: A retrospective observational single center study

Abstract: Based on the developed prognostic scores, seizure prophylaxis should be considered in high-risk patients and patient stratification for prospective studies may be feasible in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
2
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 23 publications
5
58
2
3
Order By: Relevance
“…The main results of this study are that preoperative tumor volume of the contrast enhancing tumor (not the FLAIR-hyperintense edema) shows a significant correlation to seizures. This is in common with a previous study by Skardelly et al that showed a tumor volume <64 cm 3 as a main risk factor for the development of preoperative seizures [18]. Another study showed that this association was only found in high-grade gliomas, but not in low-grade gliomas where an inverse association between tumor volume and seizures was observed [17].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The main results of this study are that preoperative tumor volume of the contrast enhancing tumor (not the FLAIR-hyperintense edema) shows a significant correlation to seizures. This is in common with a previous study by Skardelly et al that showed a tumor volume <64 cm 3 as a main risk factor for the development of preoperative seizures [18]. Another study showed that this association was only found in high-grade gliomas, but not in low-grade gliomas where an inverse association between tumor volume and seizures was observed [17].…”
Section: Discussionsupporting
confidence: 88%
“…According to this study high grade gliomas presenting with neurologic symptoms instead of seizures were more likely to occur in the pericallosal region [17]. Interestingly other than previous studies, we found no significant associations between location in the left hemisphere and infiltration of the hippocampus was associated with preoperative seizure as shown in previous studies [18,31,32]. Main explanation for this finding might be that the cited previous studies mainly assessed low-grade gliomas whereas this study only investigated glioblastoma patients only.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Brain tumors, either primary or secondary, account for 5-20% of cases of seizures occurring for the first time in adult. 7,8,37 Seizure is the first symptom in 30% of brain tumors. In adult, a first seizure, particularly if focal should be evaluated by MRI for an occult brain tumor.…”
Section: -29mentioning
confidence: 99%